THE EFFECT OF ECOPRENEURSHIP-BASED ENTREPRENEURSHIP COURSES ON THE INNOVATION ABILITY OF SCIENCE EDUCATION STUDENTS - Deliani Margarita; Rizky Febriyani Putri; Sauqina Sauqina (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
The purpose of this study was to test or analyze the effect of the implementation of ecopreneurship on Students' ability to be innovative. This research uses a quantitative approach with the type of quasi-experiment design One group pretest-posttest. The research was conducted in the Entrepreneurship course for students of the Science Education Study Program in the academic year 2024/2025 odd semester. The sample selection technique used was Purposive sampling, which is part of non-probability sampling with a research sample of 33 students who took Entrepreneurship courses. To determine the effect of the ecopreneurship-based learning on Students' ability to innovate, the Paired Sample T-Test test was used with the help of the SPSS program. Based on the calculation of the Paired Sample T-Test, the Sig value is 0.000 < 0.05, which means that there is a significant effect of the implementation of ecopreneurship on Students' capacity for innovation. The implications of this research support sustainable innovation and can be used in other courses that require the same thing as this research. The results showed that the effect of applying the Ecopreneurship concept was able to encourage students' ability to innovate in making innovative environmentally friendly products, namely by developing problem-solving skills, creating innovative ideas, designing and producing product innovations and preparing students to become entrepreneurs who have the ability to innovate.